(untitled) (ENTHYMEMA, 2017)
Le particolari condizioni in cui il Self si è costituito nelle società orientali - con una prevalenza per orientamenti interpersonali e visioni olistiche del contesto storico-ambientale - hanno radicato nella letteratura cinese, giapponese e sudcoreana il modello del family novel come un fondamento strutturale, mentre in Occidente esso ha costituito una ricorrenza relativamente rara. Mentre nelle letterature nordamericane e europee il format familiare ha svolto compiti di manutenzione simbolica delle relazioni dell’individuo con la società, in Oriente a opinione di Richard E. Nisbett il family novel è un Iper-individuo, la condizione necessaria per le narrazioni finzionali e per le life narratives individuali, come dimostrano i casi di Murakami Haruki, Su Tong e Mo Yan. The specific conditions in which the Self has established itself in Eastern societies – namely the prevalence for interpersonal orientations and holistic views of the historical-environmental context – have established the family novel model as a structural foundation in the Chinese, Japanese, and South Korean literature. On the contrary, in the West the same pattern has been a relatively rare occurrence. While in North American and European literatures, the family format has carried out symbolic maintenance tasks about the relationships between individuals and society, in the East, according to Richard E. Nisbett, the family novel is a hyper-individual, the necessary condition for fictional narratives and for individual life narratives, as evidenced by the cases of Murakami Haruki, Su Tong and Mo Yan.